Delivery of an Exercise Program for Breast Cancer Survivors on Treatment in a Community Setting. Issue 24 (15th December 2017) - Leach, Heather J.; Gainforth, Heather L.; Culos-Reed, S. Nicole
ABSTRACT: Purpose: Exercise can help reduce the negative physical and psychological side effects of breast cancer treatments. Breast Cancer Patients Engaging in Activity while Undergoing Treatment (BEAUTY) is an exercise program that has been operating in a university-based setting for 4 years. This study describes the feasibility of implementing BEAUTY at the YMCA following the RE-AIM framework. Methods: This is a single-center, single-cohort interventional feasibility study. Breast cancer patients undergoing or within 3 months of completing chemotherapy and/or radiation treatment ( N = 12) received individualized exercise programs and group-based exercise classes twice per week for 19 wk. Outcome variables were measured pre- and post program. Results: YMCA BEAUTY had similar reach to the university BEAUTY program in terms of recruitment rate and representativeness. Participants attended M = 10.7 ± 10.0 classes and 75% completed post program assessments. Participants showed improvement in the 6-min walk test ( M [INCREMENT] = 45.7 m). All other physical outcomes and quality of life were maintained. Overall, the program was delivered as intended, evidenced by outcomes assessed, exercise class, and education session delivery. A key component for setting level maintenance is the expertise of YMCA fitness professionals needed to deliver an exercise program for a clinical population. Conclusions: On the basis of RE-AIM metrics, BEAUTY was feasible and appears to be promising for improving health and well-being of breast cancer survivors. These findings will inform researchers, clinicians, health professionals, and fitness facilities of the implementation considerations for future community-based programs for cancer survivors undergoing treatment.